THE POTENTIAL OF FLORAL PATTERN ART IN MALAY TEXTILE EMBROIDERY: A FORMALISTIC ANALYSIS - Abdullah, Zamrudin; Musa Kahn, Sabzali; Yahaya, Siti Rohaya; Harun, Azahar; Ghazali, Rusmawati (Jurnal Pengajian Melayu (JOMAS), 2018)
This research studies the aesthetic processes of creating stylized, colourful, floral motifs on fabric. Malay fabric often include various floral motifs such as hibiscus, pitcher plant, rose and frangipani. These floral motifs have the potential to be stylized in more innovative and creative ways. Some designers and artists who are proficient in pattern design did not receive a formal education in pattern design, but their expertise and skills are impressive nonetheless. The quality and visual aesthetics of textile designs are highly dependent on the motifs created through skilled labors and design. Floral motif is not only visually appealing, but also has its own meaning and reflects the creative values of its designer. Floral motifs are representative of the affinity of Malay culture with nature. This research might inspire designers and inform current society that floral motifs can be innovated in scientific and creative manners. Furthermore, floral motifs. Keywords: Textile, Pattern design, Floral, Embroidery, Creative, Innovation.